Effect of Dry and Wet Packing on Quality of Cut Orchid Flowers of Dendrobium - - (Agriculture and Natural Resources, 1992)
The study was conducted to investigate dry and wet packing for export of orchid flowers of Dendrobium Pompadour, Dendrobium Sonnia Bomb # 28 and Dendrobium Walter Oumae Taba (2n). The results showed that orchid flowers being packed wet using small and large plastic tubes contained 3 and 4 ml distilled water, respectively and cotton balls contained 50 ml distilled water retained more freshwess than those being packed dry and wet using cotton balls contained 30 and 40 ml distilled water during simulated shipment at 25 degree C for 36 hours. Orchid flowers being packed wet using plastic tubes caused a greater decay of basal stem-end than using cotton balls during shipment. Orchid flowers being packed wet using plastic tubes had a longer vase-life than those being packed wet using cotton balls but had no significant effect on bud opening. Use of preservative solution instead of distilled water for packing wet increased the freshness and vase-life during holding at room temperature. Dendrobium Pompadour and Dendrobium Walter Oumae Taba responded to the preservative solution better than Dendrobium Sonnia Bomb # 28.